Implemention of the Integrated Management System (Quality-Environment) in the City Hall of Bucharest - IANCU Alexandra (Applied Research in Administrative Sciences)
The present research aims to highlight the importance of implementing the Integrated Management System (IMS) in the General City Hall of Bucharest and, thus, producing positive effects such as: efficient allocation of resources by improving forecasting and planning, increasing the quality of services provided to citizens, improving communication between departments of the institution, reducing the number of complaints made by citizens about the quality of public services, changing the organisational structure by resizing the departments of the institution, increasing the transparency of the decision-making process. The research is based on the combined use of several methods: analysis of official documents (reports, analysis of performance indicators that are established at the level of each department within the City Hall of Municipality of Bucharest (PMB) according to the services they provide to customers/citizens and are reported periodically, being a key tool for the management of the organisation) and opinion survey based on the questionnaire addressed to civil servants within the City Hall. The results prove that the maintenance and improvement of the Integrated Management System in the PMB requires a permanent involvement of the management of the directorates for the implementation of the processes carried out in the institution.